1996
DOI: 10.1111/j.1365-2125.1996.tb00185.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and excretion of sumatriptan in human milk

Abstract: 1 The excretion of a 6 mg subcutaneous dose of sumatriptan in breast milk was studied in five lactating volunteer subjects with a mean age of 27.6 years and a mean body weight of 75 kg. Drug concentrations in milk and plasma over the ensuing 8 h were measured by high‐performance liquid chromatography. 2 The mean milk:plasma ratio estimated from the areas under the milk and plasma concentration‐time curves (AUC) was 4.9 (95% CI 4.1–5.7), indicating a significant transfer of sumatriptan into the milk compartment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(26 citation statements)
references
References 14 publications
3
22
0
1
Order By: Relevance
“…A published study of 5 lactating women showed no adverse pediatric events. 21 LRC L3. Briggs category: probably compatible.…”
Section: Resultsmentioning
confidence: 99%
“…A published study of 5 lactating women showed no adverse pediatric events. 21 LRC L3. Briggs category: probably compatible.…”
Section: Resultsmentioning
confidence: 99%
“…One study including five lactating women treated with a single, subcutaneous dose of sumatriptan found that the estimated RID was only 3.5%, suggesting that use of sumatriptan during lactation should not pose a substantial risk to the infant. 107 The Summary of Product Characteristics for sumatriptan Box 1 | Breastfeeding and relative infant dose Relative infant dose (RID) 101 is the weight-adjusted dose of a drug received by the infant via breast milk, expressed as a percentage of the weight-adjusted maternal dose.…”
Section: Triptansmentioning
confidence: 99%
“…Sumatriptan and eletriptan levels have been measured in human milk. For sumatriptan, the M/P ratio was 4.9:1, with 0.21% of peak plasma dose measured at 8 hours after 6 mg of the subcutaneous dose was given [33]. Eletriptan had an M/P ratio of 1:4, with 0.02% of an 80-mg dose measured at 24 hours [32].…”
Section: Drug Safety During Lactationmentioning
confidence: 99%